Visualization systems supporting the reading of arabic document for non arabic speakers - Yusof, R.J.R.; Zainuddin, R.; Baba, M.S.; Yusoff, Z.M. (2009)
This study addresses a reading comprehension problem and visualization as the suggested solution. When one read, one would intend to understand the text being read. It is absolutely an exception in the context of one Arabic document called the Quran. Thus, visualization techniques are then useful to support the understandability of the document for non-Arabic speakers such as the Malaysian and Indonesians. Descriptions and review of four prototype systems that use visualization techniques: scatter plot, trivariate plot, network diagrams, directory approach and hyperbolic. This study discusses reading and visualization theories, the problems encountered while reading the Arabic document (the Quran), comparative discussions on the prototype systems and functional requirement proposed to enhance the prototype. Â© 2009 Asian Network for Scientific Information.